An Alternative Econometric Approach to the Permanent Income Hypothesis: An International Comparison - Singh, Balvir; Drost, Helmar (The Review of Economics and Statistics, 1971)
Balvir Singh, Helmar Drost, An Alternative Econometric Approach to the Permanent Income Hypothesis: An International Comparison, The Review of Economics and Statistics, Vol. 53, No. 4 (Nov., 1971), pp. 326-334